GEOCHRONOLOGY OF ANTHROPOGENIC METAL CONTENT FROM CORAL PORITES SP. IN KEPULAUAN SERIBU - Irsyad Wijanto, Raihan
Indonesia is located in the Coral Triangle of Southeast Asia. The Coral Triangle of Southeast Asia is a fertile area where coral reefs grow well. However, the impact of human activities (anthropogenic) can cause a decrease in seawater quality, which becomes one world concern because it impacts marine life and the ecosystem in it. Coral is an alternative geochronological analysis that can see the chronology (history) of heavy metal concentrations each year. The Thousand Islands waters are an area with high marine biodiversity because anthropogenic influences such as boat activity and tourism threaten coral reefs. In this study, the corals of the two islands, Pramuka Island and Pari Island, were studied to show a geochronology analysis for 36 years (1983-2018) and show the chronology of metal concentrations. These studies show that metal associations formed in the Thousand Islands' waters could explain the metal source (anthropogenic or conservative). The results in Pari Island show that Ferrum (Fe) and Aluminum (Al) metals are in one group, Copper (Cu) and Zinc (Zn) metals come from the same source, classified as anthropogenic metals. In the metal association in Pramuka Island, iron metal (Fe) stands alone, while aluminum (Al), copper (Cu), and zinc (Zn) metal comes from the same group, which is classified as an anthropogenic metal. The Enrichment Factor's value indicates the metal contamination as an indicator of water pollution in the area. This enrichment factor's value showed that the Cu metal in the two samples (Pari Island and Pramuka Island) was sufficiently enriched (contaminated) with an average value of EF = 5.84 in Pari Island and EF = 6.46 in Pramuka Island. Overall, Zn did not show any enrichment (uncontaminated) with an average EF = 1.46 for Pari Island and an average EF = 1.07 for Pramuka Island. With sufficient enrichment results, the EF Cu value in Pramuka Island is greater than the EF Cu on Pari Island closer to the mainland (Jakarta). The results concluded that Pari Island and Pramuka Island were contaminated by Cu metal by contaminants originating from local waters and were not affected by pollutants from Jakarta's mainland. The seasonal flow current confirms the absence of a current pattern leading to the study area from the direction of the mainland (Jakarta) where the transitional seasons 1, 2, and the east monsoon indicate the flow's direction to the southwest. In contrast, only one month in the west monsoon, the ocean currents show the northeast direction. This seasonal flow current does not play a role in bringing particles from the mainland (Jakarta) to Pari Island and Pramuka Island.